Adipocytes from New Zealand Obese Mice Exhibit Aberrant Proinflammatory Reactivity to the Stress Signal Heat Shock Protein 60 - Tina Märker; Jennifer Kriebel; Ulrike Wohlrab; Volker Burkart; Christiane Habich (Journal of Diabetes Research)
Adipocytes release immune mediators that contribute to diabetes-associated inflammatory processes. As the stress protein heat shock protein 60 (Hsp60) induces proinflammatory adipocyte activities, we hypothesized that adipocytes of diabetes-predisposed mice exhibit an increased proinflammatory reactivity to Hsp60. Preadipocytes and mature adipocytes from nonobese diabetic (NOD), New Zealand obese (NZO), and C57BL/6J mice were analyzed for Hsp60 binding, Hsp60-activated signaling pathways, and Hsp60-induced release of the chemokine CXCL-1 (KC), interleukin 6 (IL-6), and macrophage chemoattractant protein-1 (MCP-1). Hsp60 showed specific binding to (pre-)adipocytes of NOD, NZO, and C57BL/6J mice. Hsp60 binding involved conserved binding structure(s) and Hsp60 epitopes and was strongest to NZO mouse-derived mature adipocytes. Hsp60 exposure induced KC, IL-6, and MCP-1 release from (pre-)adipocytes of all mouse strains with a pronounced increase of IL-6 release from NZO mouse-derived adipocytes. Compared to NOD and C57BL/6J mouse derived cells, Hsp60-induced formation of IL-6, KC, and MCP-1 from NZO mouse-derived (pre-)adipocytes strongly depended on NFκB-activation. Increased Hsp60 binding and Hsp60-induced IL-6 release by mature adipocytes of NZO mice suggest that enhanced adipocyte reactivity to the stress signal Hsp60 contributes to inflammatory processes underlying diabetes associated with obesity and insulin resistance.